Upper limb injuries associated with rock climbing. Issue 2 (June 1986) - Bannister, P; Foster, P
Abstract : Four cases of upper limb injuries secondary to rock-climbing or training for rock climbing are presented. All four cases had diagnosis and treatment delayed because of unawareness of the range of injuries seen in high grade rock climbing.